2016
DOI: 10.21608/assjm.2016.103906
|View full text |Cite
|
Sign up to set email alerts
|

Sugar beet yield and quality as affected by concentration of boron and methanol application.

Abstract: The aim of this research is to assess the effect of foliar spraying with boron and methanol levels and time of methanol application. Two field experiments were conducted at EL-Haamoul district Kafer EL-Sheikh Governorate, Egypt during 2012/2013 and 2013/2014 seasons. Strip-plot design was used in both seasons. Main plot (vertical) allocated with Boron levels (0, 1 and 1.5 Kg/fed.) sub plot (horizontal plots) takes Methanol rates (15%, 30% and 45% v/v) this solution were sprayed overhead 3 times in two weeks in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…The pronounced effect of boron on root length may be due to its effect on the growth which in turn affect root length of sugar beet. The results of boron on root length obtained in the study are in agreement with those obtained by Ahmed ( 2005), Moustafa and Omran (2006), Taha et al (2013) andNemeat Alla et al (2016).…”
Section: Results and Discussion B -Yield Components: -1-root Length (Cm)supporting
confidence: 92%
See 3 more Smart Citations
“…The pronounced effect of boron on root length may be due to its effect on the growth which in turn affect root length of sugar beet. The results of boron on root length obtained in the study are in agreement with those obtained by Ahmed ( 2005), Moustafa and Omran (2006), Taha et al (2013) andNemeat Alla et al (2016).…”
Section: Results and Discussion B -Yield Components: -1-root Length (Cm)supporting
confidence: 92%
“…This finding may be due to the healthy role of boron on the plant grown which directly affected growth vigor of the plants. This result is in harmony with those obtained by Ahmed (2005), Moustafa and Omran (2006), Taha et al (2013) andNemeat Alla et al (2016). reported that top yield was significantly affected by boron.…”
Section: C-yield Attributes: -1-top Yield (Ton/fad)supporting
confidence: 91%
See 2 more Smart Citations
“…In addition, Sogut and Arioglu [9] reported that plant density at 148 148, 111 111, and 88 889 produced higher root yields than 74 074 and 63 492 plants per hectare. Nemeat-Alla [10] reported that planting sugar at a population of 100 000 plants ha −1 caused significant increases in root diameter but did not affect root length and total soluble solids. On the other hand, Bhullar et al [11] stated that the plant population of 100 000 plants ha −1 produced the lowest beetroot diameter and highest root length and root yields.…”
Section: Introductionmentioning
confidence: 99%